Question
upstudy study bank question image url

Use implicit differentiation to find \( \frac{d y}{d x} \). \[ 9 x y+y^{2}=2 x+y \]

Ask by Clarke Mann. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \frac{dy}{dx} = \frac{2 - 9y}{9x + 2y - 1} \]

Solution

We start with the equation   9xy + y² = 2x + y. To find dy/dx using implicit differentiation, differentiate both sides of the equation with respect to x. Step 1. Differentiate each term: • For 9xy, use the product rule (derivative of x·y is y + x·(dy/dx)):   d/dx[9xy] = 9(x·(dy/dx) + y). • For y², use the chain rule:   d/dx[y²] = 2y · (dy/dx). • For 2x, the derivative is:   d/dx[2x] = 2. • For y, the derivative is:   d/dx[y] = dy/dx. Step 2. Write the differentiated equation:   9(x·(dy/dx) + y) + 2y·(dy/dx) = 2 + (dy/dx). Step 3. Expand and gather like terms:   9x·(dy/dx) + 9y + 2y·(dy/dx) = 2 + (dy/dx). Bring all terms involving dy/dx to one side by subtracting (dy/dx) from both sides:   9x·(dy/dx) + 2y·(dy/dx) − (dy/dx) = 2 − 9y. Factor out dy/dx from the left side:   (9x + 2y − 1)·(dy/dx) = 2 − 9y. Step 4. Solve for dy/dx:   dy/dx = (2 − 9y) / (9x + 2y − 1). Thus, the derivative dy/dx is given by   dy/dx = (2 − 9y) / (9x + 2y − 1).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find \( \frac{dy}{dx} \) using implicit differentiation for the equation \( 9xy + y^2 = 2x + y \), we'll differentiate both sides with respect to \( x \). Starting with the left side, for \( 9xy \), we apply the product rule: \[ \frac{d}{dx}(9xy) = 9\left(x\frac{dy}{dx} + y\right) \] For \( y^2 \): \[ \frac{d}{dx}(y^2) = 2y\frac{dy}{dx} \] Now differentiating the right side: \[ \frac{d}{dx}(2x) = 2, \quad \text{and} \quad \frac{d}{dx}(y) = \frac{dy}{dx} \] Putting everything together gives us: \[ 9\left(x\frac{dy}{dx} + y\right) + 2y\frac{dy}{dx} = 2 + \frac{dy}{dx} \] Now, we can combine like terms: \[ (9x + 2y - 1)\frac{dy}{dx} + 9y = 2 \] Isolating \( \frac{dy}{dx} \): \[ (9x + 2y - 1)\frac{dy}{dx} = 2 - 9y \] Finally, we solve for \( \frac{dy}{dx} \): \[ \frac{dy}{dx} = \frac{2 - 9y}{9x + 2y - 1} \] And there you have it! \( \frac{dy}{dx} = \frac{2 - 9y}{9x + 2y - 1} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy